2022
DOI: 10.1186/s12870-022-03678-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, phylogeny and expression analysis of the SPL gene family and its important role in salt stress in Medicago sativa L.

Abstract: Background SQUAMOSA promoter-binding protein-like (SPL) transcription factors are widely present in plants and are involved in signal transduction, the stress response and development. The SPL gene family has been characterized in several model species, such as A. thaliana and G. max. However, there is no in-depth analysis of the SPL gene family in forage, especially alfalfa (Medicago sativa L.), one of the most important forage crops worldwide. Result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…MEME (Multiple Em for Motif Elicitation) tool (5.4.1 version, https://meme-suite.org/meme/tools/meme ) [ 59 ] was employed for the analysis of conserved motifs from DREB proteins in G. barbadense , G. hirsutum , G. arboreum , and G. raimondii . The phylogenetic trees and conserved motifs were integrated by using TBtools software.…”
Section: Methodsmentioning
confidence: 99%
“…MEME (Multiple Em for Motif Elicitation) tool (5.4.1 version, https://meme-suite.org/meme/tools/meme ) [ 59 ] was employed for the analysis of conserved motifs from DREB proteins in G. barbadense , G. hirsutum , G. arboreum , and G. raimondii . The phylogenetic trees and conserved motifs were integrated by using TBtools software.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have proven that squamosa promoter-binding-like protein (SPL) can regulate salt tolerance in many plants, such as apple [ 9 ], alfalfa ( Medicago sativa L.) [ 72 ], and tamarisk ( Tamarix chinensis ) [ 57 ]. Recent research showed that silencing CaSBP12 in pepper ( Capsicum annuum ) enhances tolerance to salt stress and reduces ROS accumulation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Vitis pseudoreticulata VpSBP16 could enhance the scavenging ability of ROS to enhance the salt tolerance and drought tolerance of grapes (Hou et al 2018 ). In addition, 3 differentially expressed MsSPLs ( MsSPL17 , MsSPL23 and MsSPL36 ) were found in Medicago sativa under salt stress, which provided comprehensive information for the mechanism underlying salt tolerance improvement in M. sativa (He et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%